BUILDING COOLING LOADS CALCULATION WITH LOCAL WEATHER DATA - Yousif Abdulsamad Khorsheed; Suad Hassan Danook (NTU Journal of Engineering and Technology)
In large buildings, an HVAC system established for the purpose of cooling consumes around 60% of the overall energy requirements.The purpose of this research is to determine the cooling load based on the local climate. A building with dimensions of 17 m x 13 m x 3.5 m was taken as a case study. In this research, The CLTD/CLF method is used to calculate the cooling loads. On the basis of the MATLAB V.2014b program, the appropriate codes were written. Meteonorm version 8.0.3 was used to collect detailed local climate data for an average of 20 years. the results showed that the high load occurs in August and July, respectively. The peak cooling load for August was on the 19th of August, which was 49.22 kW, and the peak cooling load for July was on the 21st of July, which was 46.4 kW.